Kajian Literatur Tentang Karakteristik dan Strategi Penanganan ADHD pada Konteks Sekolah Inklusif - Dwi Fitria, Kamila; Khusna Maulida, Lia; Chorynia Ruby, Arcivid (Indo-MathEdu Intellectuals Journal, 2025)
ADHD is a condition that causes difficulty in controlling impulses and maintaining concentration, thus affecting the learning process and social interactions of children. This study aims to identify the main characteristics of children with Attention Deficit Hyperactivity Disorder (ADHD) and to formulate literature-based and applicable treatment strategies in an inclusive school environment. A total of 9 out of 15 articles were reviewed in depth to identify the core characteristics of children with ADHD, such as inability to concentrate, impulsivity, and hyperactivity. This study is a literature review study with a descriptive qualitative approach. Data sources were obtained from scientific articles published in reputable journals between 2015 and 2024 that discussed ADHD in the context of education. Data collection techniques were carried out through systematic searches using specific keywords in online databases such as Google Scholar, ScienceDirect, and ERIC. The selected articles were selected based on certain inclusion criteria, such as topic relevance, suitability to the educational context, year of publication, and full accessibility. The data analysis technique used was content analysis, by identifying the main themes of the selected articles, so that patterns of characteristics and ADHD treatment strategies that were relevant to the inclusive school environment were obtained